EPIDEMIOLOGICAL SURVEY OF GENITAL PROLAPSE IN BUFFALOES KEPT UNDER DIFFERENT SYSTEMS AND SERUM MICRO MINERAL CONTENTS - M. S. BHATTI, I. AHMAD, N. AHMAD, L. A. LODHI AND M. AHMAD (Pakistan Veterinary Journal, 2006)
The present project was planned to conduct an epidemiological survey of genital prolapse in buffaloes kept under different feeding and production systems and to study serum micro mineral contents in these animals. Data on 343 buffaloes were recorded for epidemiological studies, including 297 normal pregnant and 46 prolapsed cases. For serum micro mineral contents, blood samples were collected from 40 buffaloes comprising of 20 normal pregnant and 20 suffering from genital prolapse and analyzed for serum Cu, Zn, Fe and Mn contents. Occurrence of genital prolapse differed non significantly in animals kept under two feeding systems (stall fed and semi stall fed), three floor conditions (uneven floor, kacha/brick floor, sloppy floor) and two production systems (rural subsistence small holding and market oriented small holding). Its occurrence was higher during humid summer than other seasons. The mean values of serum copper and zinc were lower in prolapsed buffaloes compared to controls (P<0.01), while there was no difference in serum iron and manganese concentrations among animals of the two groups. Parity had no effect on serum concentration of any micro mineral. However, serum Zn level was higher in buffaloes suffering from vaginal prolapse compared to those with uterine prolapse (P<0.05).